FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF Staphylococcus aureus MICROEMULSION OF ANTING-ANTING (Acalypha indica) LEAF EXTRACT USING ISOPROPYL MIRISTAT AS OIL PHASE - Husniyah, Jauharatul; Annisa, Rahmi; Ma'arif, Burhan (Journal of Islamic Pharmacy, 2018)
Leaf of Anting-Anting (Acalypha indica) is one of the plants that contain potent flavonoid compounds as antibacterial Staphylococcus aureus. The purpose of this research is to know physical characteristic of microemulsion of A. Indica leaf extract and to know antibacterial activity against Staphylococcus aureus bacteria. The microemulsions in this study used isopropyl myristate as the oil phase, tween 80 and span 80 as surfactant, isopropanol as kosurfactant and free water from CO2. Microemulsion was made by varying the concentration of the extract into 3 formulas, there are 5%, 10% and 15%. A. indica extract obtained using ultrasonic maseration extraction method with 70% ethanol solvent. All the formulas were evaluated for the characteristics of the preparations and the antibacterial activity test against Staphylococcus aureus bacteria with the sumuran diffusion method. The research results showed that the microemulsion of A. indica leaf extract has good physical characteristic with pH value between 4.9-5.8, deep oil type, that particle size F1 9.34 μm, F2 14.22 μm and F3 9.68 μm and stable physically at 25°± 2°C and 40°± 2°C. The result of antibacterial activity test showed that F1 did not differ significantly with positive control. However, the inhibitory power of F1 is still under positive clindamycin control of 12.98 mm and 15.05 mm. So it can be collected that F1 is an ideal formula which has good physical characteristics and has optimum drag power.